Immunological Sequelae of Trichinella spiralis Infection in Mice II. Potentiation of Cell-Mediated Response to BCG After Infection with Trichinella spiralis - Cypess, R. H. (1974)
Mice were infected with 200 Trichinella spiralis 14 days after intravenous administration of 4 × 10(6) viable BCG cells. Individual groups were tested for delayed hypersensitive footpad responses at 14, 20, 29, 57, or 85 days after T. spiralis infection. An initial suppression in the 14-day test group was observed; however, mice tested at later time intervals exhibited potentiation of the 24-h footpad reaction to old tuberculin over that elicited by appropriate controls. This suggested that T. spiralis induces a potentiation of the cellular immune response to BCG. Adoptive transfer studies support the cell-mediated nature of the observed footpad reaction and indicated that the initial suppression was not due to physiological factors preventing the expression of the footpad swelling reaction.